Modulating the human gut microbiome as an emerging therapeutic paradigm. (1st September 2013) - Rajpal, Deepak; Brown, James
The human body is actually a vast and changing ecosystem comprised of billions of microbial organisms, known collectively as the microbiome. within the last few years, the study of the microbiome and its impact on human health has been a rapidly growing area of biomedical science. The gut intestinal tract microbiome has been a particular focus of research given its potential role in many inflammatory and metabolic diseases as well as drug metabolism. Although a nascent field, the potential for modulating the gut microbiome or human host interactions associated with these microbes offers new therapeutic strategies for many chronic diseases, in particular obesity, diabetes and inflammatory bowel diseases. Here we provide an overview of present knowledge about the gut microbiome, its putative role in metabolic diseases and the potential for microbiome focused treatments from the drug development perspective.